Gas dynamics during the sphere moving in the stationary gaseous environment - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper developed a mathematical model of the gas dynamic fluid flow around the sphere. There are three areas of different mechanisms of the interaction of moving spheres and stationary gaseous environment. It has been proved that shear flow plays a decisiverole at sphere low velocities, while at sphere velocities close to the speed of sound the critical role is exerted by the impact interaction of the sphere with the center in the front hemisphere. The shear flow behind the sphere makes a cone with stationary gaseous environment. The principle which defines the size of the cone has been established.